Study on Osmotic Consolidation and Hydraulic Conductivity Behavior of an Expansive Soil Inundated with Sodium Chloride Solution - S. Sathyapriya; R. Sharvesh; V. Karthik; Selvakumar Periyasamy; Venkatesa Prabhu Sundramurthy (International Journal of Chemical Engineering)
Canals are a very imperative source of irrigation for the agricultural sector in India. Seepage causes major water loss in canals, and hence, the installation of liners becomes necessary. Compacted clay soils are commonly used as liners in the canals. This structure will most probably be subjected to salinization and desalinization cycles throughout its life. Because of the interaction between the pore liquid and clay particles, physico-chemical influences considerably impact the behavior of clay barriers. In this paper, the effect of interacting fluid on volume change, consolidation parameters, and hydraulic conductivity of compacted clay soil is investigated with the help of a one-dimensional consolidation test. The compacted clay specimens were immersed alternatively with distilled water (DW) and sodium chloride (NaCl) solutions (SW) at constant loading of 10 kPa, which replicates the load conditions in the field canal due to 1 m head of water and incremental loading as per IS 2720 part 15 standards. The experimental results proved that there is a percentage volume change increase of about two times for each stage inundated with 4M NaCl solution than its preceding stages inundated with distilled water at constant loading of 10 kPa. The consolidation rate was accelerated with 4M NaCl solution than the normal consolidation at incremental loading. The permeability coefficient in the salt water-induced sample increased by 217% more than the distilled water-induced sample at incremental loading. Therefore, the soil specimen subjected to alternate salinization and desalinization cycles significantly affects the volumetric and consolidation behavior, leading to decreased life of clay barrier structures.